COMPARATIVE ANALYSIS OF I‘RAB IN AL-TABARI AND AL-MISHBAH TAFSIR: IMPLICATIONS FOR QUR'ANIC MEANING VARIATIONS - Siti Nurdinah; Ahmad Mantiq Alimuddin; Resy Mulyani; Dewi Sartika; Delima Afriyanti; Septi Alhani Asyifa (Lingeduca: Journal of Language and Education Studies, 2026)
Differences in i'rab analysis in Qur'anic exegesis have the potential to produce variations in meaning that impact theological, legal, and semantic aspects; however, comparative studies on its application in classical and contemporary exegesis remain limited. This study aims to analyze the comparative use of i'rab in Tafsir Al-Tabari and Tafsir Al-Mishbah and to explain its implications for variations in the meaning of the Qur'an. The study employs a qualitative approach using library research through a comparative (muq?ran) method. The data were analyzed based on five purposefully selected verses, including: Surah Ali ‘Imran [3]: 7, Surah Al-Ma’idah [5]: 6, Surah Al-Waqi’ah [56]: 79, Surah Al-A?zab [33]: 33, and QS Al-Baqarah [2]: 37. The analysis involved comparing i'rab forms, linguistic arguments, the use of qira'at and riwayat, as well as their implications for interpretation in both exegetical works. The results of the study show that in QS ?li 'Imr?n [3]: 7 and QS Al-Ma’idah [5]: 6, differences in i'rab have direct implications for theological interpretation and the establishment of legal rulings, whereas in QS Al-Waqi’ah [56]: 79, QS Al-A?zab [33]: 33, and QS Al-Baqarah [2]: 37, the function of i'rab develops through syntactic relations, the determination of referents, and the elaboration of meaning. Al-Tabari tends to use i'rab as the basis for tarjih, combined with qira'at and riwayat, whereas Quraish Shihab integrates grammatical analysis with historical, social, and contextual approaches. This study shows that i'rab not only serves to explain grammatical structure but also forms the basis for the formation of variations in meaning in accordance with each exegete’s methodological orientation.